Réponses

2013-04-30T12:33:48+02:00

 2x + 3 = 5x - 5 
2x +3-3 = 5x -5 -3
2x - 5x = -8
-3x = -8
x = -8/-3
x = 8/3 

2013-04-30T12:40:47+02:00

on met les x d'un côté et les nombres de l'autre  et on change les signes 

soit       2x+3=5x-5

              3+5  = 5x-3x

               8     =  2x

               2x=   8

                 x= 8/2 

                 x= 4

 

4-(x+2)=3+(x-2)

je ne veux pas te donner une mauvaise réponse

 

 

4x+8  =0

4x       = -8

   x      = -8/4

   x      = -2

 

6x+2 =0

6x=-2

x=-2/6

x=-1/3

 

S ={-2;-1/3}